Techniques laitières domestiques et conception du monde microbien laitier en Mongolie - Sandrine Ruhlmann (Revue d'ethnoécologie)
This article shows how, in the years 2000-2020, Mongolian nomadic herders are taking into consideration, in their practices and in their discourses, the bacteria in the fabrication of dairy products. The technical devices implemented ensure the elimination of “bad bacteria” and the development of “good bacteria”. The analysis of dairy technology allows to draw the shape of a Mongolian conception of the bacterial world of dairy products which, in the post-communist context of democratization and globalization, consists of an art of composition between different systems, notably Buddhism, shamanism, hygienic communism, and international sanitary standardization.